Diet and exercise in uterine cancer survivors (DEUS pilot) - piloting a healthy eating and physical activity program: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Koutoukidis, Dimitrios; Beeken, Rebecca; Manchanda, Ranjit; Burnell, Matthew; Knobf, M.; Lanceley, Anne
Abstract Background Endometrial cancer survivors comprise a high-risk group for obesity-related comorbidities. Healthy eating and physical activity can lead to better health and well-being, but this population may experience difficulties adopting healthy lifestyle practices. Personalised behaviour change programmes that are feasible, acceptable and cost-effective are needed. The aim of this trial is to pilot a manualised programme about healthy eating and physical activity. Methods/design This is a phase II, individually randomized, parallel, controlled, two-site, pilot clinical trial. Adult endometrial cancer survivors (n = 64) who have been diagnosed with endometrial cancer within the previous 3 years and are not on active treatment will be invited to participate. Participants will be assigned in a 1:1 ratio through minimisation to either an 8-week, group-based, behaviour-change programme with weekly 90-min sessions about healthy eating and physical activity or usual care. The intervention will focus on self-monitoring, goal setting and self-rewards. Follow-up assessments will be conducted at 8 and 24 weeks from the baseline assessment. Primary feasibility outcomes will include rates of recruitment, adherence, and retention. Discussion The study results will inform the development of a definitive randomised controlled trial to test if the programme can improve the health and quality of life of this population. It will also provide guidance on costing the intervention and the health care resource use in this population. Trial Registration ClinicalTrials.gov identifier: NCT02433080, 20 April 2015.